PENDIDIKAN AGAMA ISLAM DI ERA KOMPLEKSITAS MORAL: PENDEKATAN MAQASID SYARIAH DAN PSIKOLOGI REMAJA - Mardhatillah Mardhatillah (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This article explores the urgency of reforming the approach to Islamic Religious Education (PAI) in the face of contemporary moral complexities among youth, including pornography, bullying, relational violence, and identity crises. The normative approach in the PAI curriculum and textbooks is found to be increasingly irrelevant to students' psychosocial needs. Using a qualitative case study at SMPN 9 Banda Aceh, the study reveals that most students desire a more realistic and contextual religious education. The article proposes integrating Maqasid Syariah particularly hifz al-aql, hifz al-nafs, and hifz al-din with developmental psychology theories (Kohlberg and Erikson), while emphasizing project-based pedagogy, moral reflection, and collaborative engagement between schools, families, and communities. The study recommends developing PAI modules that are practical, adaptive, and responsive to the moral dynamics of modern adolescents.